HISTORY OF AFRICAN SLAVERY IN PERU FROM THE CONQUEST TO ABOLITION - Arrelucea, Maribel (2004)
This article refers to the arriving of slaves to Peru, their daily live in the different places where they lived and where they were carried, the wealth of their cultural contribution, and the different ways to confront slavery: from complete passivity to open rebelliousness. Without impassioned and cultural limits, I think that the Sesquicentennial of the abolition of the slavery in Peru, would be an opportunity to learn more from the past and to think about the future of afro-peruvian people.